Predicting Employees’ Intention to stay in the Hotel Industry: A Cross-national Comparison between China and Malaysia - Ma, Weina; Yong, See Chen (International Journal of Global Economics and Management, 2024)
This study investigates the factors influencing employees’ intention to stay in the hotel industry through a cross-national comparison between China and Malaysia. By analyzing survey data from 190 employees in China and 181 in Malaysia, the research explores the effects of pay and compensation, career advancement, and performance appraisal on retention intentions and how these effects are moderated by nationality. The results indicate that all three factors significantly influence employees’ intention to stay in both countries. However, the impact of pay and compensation, and performance appraisal is notably moderated by nationality, with significant variations observed between the two countries. Specifically, while pay and compensation and performance appraisal are crucial for retention in both China and Malaysia, career advancement opportunities are more critical for employees in Malaysia. These findings highlight the necessity for hotel management to tailor their human resource practices to fit the cultural and economic contexts of each country. In China, improving compensation and performance appraisal systems is essential for enhancing retention, whereas in Malaysia, offering robust career advancement opportunities is key. The study extends Herzberg’s two-factor theory by demonstrating how motivational and hygiene factors’ significance varies with cultural and economic contexts, contributing valuable insights into how nationality influences employee retention strategies. Limitations of this research include its cross-sectional design and reliance on self-reported data. Future research should consider longitudinal studies and include a broader range of countries to validate and extend these findings. Exploring additional factors such as job satisfaction and work-life balance could further enrich understanding of employee retention dynamics in the hospitality industry.